Efektivitas Program Taman Maju Bersama dalam Pengelolaan Ruang Terbuka Hijau di DKI Jakarta - Dita Rahmaditiani Junaidi; Rahmat Salam (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Green Open Space (RTH) has an important role in creating a healthy urban environment and improving the welfare of the community. In DKI Jakarta, as the capital city of Indonesia which is densely populated and experiencing rapid urbanization, the management of green open space is becoming increasingly important. This study aims to determine and analyze the effectiveness of the Taman Maju Bersama program in managing green open space in South Jakarta and East Jakarta. The type of research that will be carried out in this study is qualitative research using the type of case study research. For data collection techniques in researching the effectiveness of the Taman Maju Bersama program in managing green open space in the South Jakarta and East Jakarta Regions, namely using observation, interviews and documentation. The results showed that the green space management program was effective in achieving several individual goals, such as increasing green area and community participation. However, there are significant challenges related to budget constraints, policy changes, and coordination among stakeholders that affect the overall effectiveness of the program. Although community satisfaction was relatively positive, especially with regard to the presence of green open spaces, there is a need to improve project management, community participation, and resource utilization.